YES Problem: f(x1) -> n(c(n(a(x1)))) c(f(x1)) -> f(n(a(c(x1)))) n(a(x1)) -> c(x1) c(c(x1)) -> c(x1) n(s(x1)) -> f(s(s(x1))) n(f(x1)) -> f(n(x1)) Proof: String Reversal Processor: f(x1) -> a(n(c(n(x1)))) f(c(x1)) -> c(a(n(f(x1)))) a(n(x1)) -> c(x1) c(c(x1)) -> c(x1) s(n(x1)) -> s(s(f(x1))) f(n(x1)) -> n(f(x1)) Matrix Interpretation Processor: dim=3 interpretation: [1 0 1] [s](x0) = [0 0 0]x0 [0 0 0] , [1 0 0] [a](x0) = [0 1 0]x0 [0 0 0] , [1 0 0] [0] [c](x0) = [0 0 0]x0 + [1] [0 0 0] [0], [1 0 0] [0] [f](x0) = [0 0 0]x0 + [1] [0 1 1] [0], [1 0 0] [0] [n](x0) = [0 0 0]x0 + [1] [0 1 1] [1] orientation: [1 0 0] [0] [1 0 0] [0] f(x1) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = a(n(c(n(x1)))) [0 1 1] [0] [0 0 0] [0] [1 0 0] [0] [1 0 0] [0] f(c(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = c(a(n(f(x1)))) [0 0 0] [1] [0 0 0] [0] [1 0 0] [0] [1 0 0] [0] a(n(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = c(x1) [0 0 0] [0] [0 0 0] [0] [1 0 0] [0] [1 0 0] [0] c(c(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = c(x1) [0 0 0] [0] [0 0 0] [0] [1 1 1] [1] [1 1 1] s(n(x1)) = [0 0 0]x1 + [0] >= [0 0 0]x1 = s(s(f(x1))) [0 0 0] [0] [0 0 0] [1 0 0] [0] [1 0 0] [0] f(n(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = n(f(x1)) [0 1 1] [2] [0 1 1] [2] problem: f(x1) -> a(n(c(n(x1)))) f(c(x1)) -> c(a(n(f(x1)))) a(n(x1)) -> c(x1) c(c(x1)) -> c(x1) f(n(x1)) -> n(f(x1)) WPO Processor: algebra: Sum weight function: w0 = 0 w(c) = w(n) = w(a) = w(f) = 0 status function: st(c) = st(n) = st(a) = st(f) = [0] precedence: f > a > c ~ n problem: Qed